2012
DOI: 10.1515/bc-2011-193
|View full text |Cite
|
Sign up to set email alerts
|

Reactive cysteine in the active-site motif of Bacteroides thetaiotaomicron dipeptidyl peptidase III is a regulatory residue for enzyme activity

Abstract: Dipeptidyl peptidase III (DPP III), a member of the metallopeptidase family M49, was considered as an exclusively eukaryotic enzyme involved in intracellular peptide catabolism and pain modulation. In 2003, new data on genome sequences revealed the first prokaryotic orthologs, which showed low sequence similarity to eukaryotic ones and a cysteine (Cys) residue in the zinc-binding motif HEXXGH. Here we report the cloning and heterologous expression of DPP III from the human gut symbiont Bacteroides thetaiotaomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 34 publications
2
33
0
Order By: Relevance
“…The 100-kDa putative DPP3 (M r ϭ 102,897 in Val 2 -Glu 906 with vector tag M r ϭ 1416.5) exhibited activity with a preference for Arg at the P1 position and the highest activity for Arg-Arg-MCA (Fig. 2B), in accord with the properties of eukaryotic (36) and Bacteroides thetaiotaomicron DPP3 (37). Therefore, PGN_1645 truly represents P. gingivalis DPP3.…”
Section: Dipeptide Production In P Gingivalis Wild Type and Kdp136-mentioning
confidence: 56%
See 1 more Smart Citation
“…The 100-kDa putative DPP3 (M r ϭ 102,897 in Val 2 -Glu 906 with vector tag M r ϭ 1416.5) exhibited activity with a preference for Arg at the P1 position and the highest activity for Arg-Arg-MCA (Fig. 2B), in accord with the properties of eukaryotic (36) and Bacteroides thetaiotaomicron DPP3 (37). Therefore, PGN_1645 truly represents P. gingivalis DPP3.…”
Section: Dipeptide Production In P Gingivalis Wild Type and Kdp136-mentioning
confidence: 56%
“…Therefore, PGN_1645 truly represents P. gingivalis DPP3. However, the observation that KDP136 did not hydrolyze Arg-Arg-MCA strongly suggested that DPP3 did not participate in extracellular dipeptide production in P. gingivalis and that it may be localized in the cytoplasm, as reported for B. thetaiotaomicron DPP3 (37).…”
Section: Dipeptide Production In P Gingivalis Wild Type and Kdp136-mentioning
confidence: 76%
“…Production of recombinant human DPP III was performed according to Š poljarić et al 28 . Gene amplification and expression of DPP III from Bacteroides thetaiotaomicron was described by Vukelić et al 16 . Protein purity was confirmed by SDS-PAGE according to Laemmli 29 .…”
Section: Synthesis Of the Hydroxamate Inhibitorsmentioning
confidence: 99%
“…These first two prokaryotic orthologs (from P. gingivalis and B. thetaiotaomicron) helped us to define five conserved regions in the peptidase family M49 14 . We have cloned and biochemically characterized the first bacterial DPP III, from the human gut symbiont B. thetaiotaomicron, revealing similarities but also important differences compared to its human counterpart 16 . Until now, crystal structures of two M49 family members have been solved, yeast and human DPP III 17,18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation